NARCOMANIAS, TOXICOMANIAS, POISONINGS - P. F. Litvitskii (Вопросы современной педиатрии, 2014)
The reasons, risk factors, key links of mechanisms of development, manifestation and the principles of treatment of narcomanias and toxicomanias are discussed in the lecture. Tests for the assessment of the retention level of its material and also variants of answers to them are attached to the lecture.